Exzerpieren - Kompilieren - Tradieren Transformationen des Wissens zwischen Spätantike und Frühmittelalter - Dusil, Stephan; Schwedler, Gerald; Schwitter, Raphael (Millennium-Studien / Millennium Studies, 2016)
This study examines from multiple disciplinary perspectives the phenomenon of how knowledge was transformed and transmitted between late antiquity and the Early Middle Ages. The essays explore the ways that excerpting, compiling, and selective transmission resulted in a reduction of complexity.